Exploiting thermal strain to achieve an in-situ magnetically graded material. (5th January 2019) - Freeman, Felicity S.H.B.; Lincoln, Alex; Sharp, Jo; Lambourne, Al; Todd, Iain
Abstract: Spatially resolved functional grading is a key differentiator for additive manufacturing, achieving a level of control that could not be realised by conventional methods. Here we use the rapid solidification and thermal strain associated with selective laser melting to create an in-situ microstructurally and magnetically graded single-composition material, exploiting the solid-state austenite-martensite phase transformation. The fine grain sizes resulting from high cooling rates suppress the thermal martensite start temperature, increasing the proportion of retained austenite. Then the thermal strain accrued during the build causes in-situ deformation-driven martensitic transformation. By controlling the thermal strain, through appropriate selection of build parameters and geometry, we have been able to control the final ratio of austenite to martensite. Fully austenitic regions are paramagnetic, while dual-phase regions show increasingly ferromagnetic behaviour with an increasing proportion of martensite. We exploit this to build a magnetically graded rotor which we run successfully in a synchronous motor. Graphical abstract: Highlights: A fully austenitic structure was retained in 17-4PH by using the fine grain size to completely suppress thermally-driven martensite Strain accrued during the build was used to trigger and control the extent of deformation-driven martensitic transformation The effect was shown to be sensitive to both build parameters and sample geometry A magnetically-graded single-composition material was built by tailoring the ratio of ferromagnetic martensite to paramagnetic austenite This was exploited to build a magnetically graded rotor which was run in a synchronous motor